Hazhunt : Augmented Reality App for Gamified Occupational Safety Hazard Training - Muhammad Farez, Said (Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of this project is to develop an augmented content-based app called Hazhunt augmented reality application for the use of Occupational Safety and Health training among the organizational members, which include the students and workers. The objective of this project to use AR technology for practical on-the-spot use to prevent workplace incidents and accidents and assists the user in knowing each of the icons for hazardous material. A recent study shows that the use of augmented reality technology can increase the safety of the worker and student in a dangerous working environment and also provides information in real-time about the hazard or chemical substance. In this report, usability testing has been conducted using the pre-test and post-test and also using the Instructional material motivational survey (IMMS) method. The participants for usability tests were ten university students from non-OSHA graduates (male = 4; female = 6; mean age = 23.5). The results show that Hazhunt AR has offered an excellent way to educate and handle danger to students and to empower them. For the pre-test, the mean and standard deviations are 10.9 and 1.523. The mean and standard deviation figures for post-testing are 14.6 and 1.712. The calculation of satisfaction earned the highest average of 4.8, followed by a relevance value of 4.65, a confidence value of 4.6, and attention. An attention rating with a value of 4.55 is the lowest mean score. The highest standard deviation is a relevance value of 0.590, follow by confidence 0.520, attention 0.510, and satisfaction 0.410. Therefore, it indicates that the students are pleased with the production and use of Hazhunt AR in training and learning.